POTENSI EKOLOGI SEMUT (FORMICIDAE) DI KAWASAN TAMBANG MINYAK BUMI TRADISIONAL WONOCOLO - Oktafitria, Dwi; Laily Agustina Rahmawati (Binar – Biology Natural Resources Journal, 2025)
This study aims to identify and analyse the ecological potential of ant species from the Formicidae family in the traditional petroleum mining area of Wonocolo, Bojonegoro Regency. This is important to do because the characteristics of traditional petroleum mining areas generally have simple methods and without adequate security, so the risk of pollution will result in a decrease in ant diversity as animals that live in the soil. This study was conducted descriptively by randomly determining 3 locations in the Wonocolo traditional petroleum mining area with a high density of wells. Then, ant samples were collected using the handsorting method and morphological identification was carried out to determine species names. Seven ant species were identified, namely Camponotus pennsylvanicus (black carpenter ant), Crematogaster claudiae (cocktail ant), Lasius niger (black garden ant), Linepithema sp (Argentine ant), Monomorium sp (pharaoh ant), Nylanderia pubens (carbuncle crazy ant) and Plagiolepis sp (small yellow ant). The ecological potential of each ant is also recognised as indicators of environmental health; as pest controllers; as decomposers; as part of symbiotic interactions; and as soil diggers to alter soil structure.